Sistem Penunjang Keputusan Pemilihan Teknologi ERP Menggunakan Pendekatan MFEP pada UMKM Coffee Shop - Rizki Ananda, Lidya; Sri Nadriati; Muhammad Ikhlas; Chandra Kusuma; Julianto Simatupang (ITB Ahmad Dahlan Jakarta, 2025)
The rapid development of digital technology requires various business sectors, including coffee shops, to adopt systems that improve operational efficiency and service quality. Enterprise Resource Planning (ERP) is a strategic solution to integrate various business processes centrally. However, the wide variety of ERP options with different features and costs necessitates an appropriate evaluation method to select the system that best fits business needs. This study uses the Multi-Factor Evaluation Process (MFEP) method to assist coffee shops in choosing the best ERP technology based on criteria such as cost, features, user-friendliness, security, and technical support. The results indicate that Odoo ERP is the recommended option due to its modularity, ease of use, cost flexibility, and adequate community and technical support. Proper ERP implementation is expected to enhance efficiency, effectiveness, and competitiveness of coffee shop businesses in an increasingly competitive market.